1997
DOI: 10.1021/la970091m
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Height and Phase Images in Tapping Mode Atomic Force Microscopy. Study of Phase-Separated Polymer Blends of Poly(ethene-co-styrene) and Poly(2,6-dimethyl-1,4-phenylene oxide)

Abstract: Blends of two polymers, poly(ethene-co-styrene) (PES) and poly(2,6-dimethyl-1,4-phenylene oxide) (PPO), were examined with tapping mode atomic force microscopy (AFM) using various values of the driving amplitude A 0 and set-point amplitude ratio r sp = A sp/A 0, where A sp is the set-point amplitude. In height and phase images of PPO/PES blend samples, the relative contrast of chemically different regions depends sensitively on the r sp and A 0 values. As the tip−sample force is increased from small to large, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
330
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(351 citation statements)
references
References 30 publications
17
330
0
4
Order By: Relevance
“…Por meio do monitoramento da diferença de fase entre a oscilação da haste e o sinal padrão, que movimenta a cerâmica piezoelétrica durante a varredura, é possível detectar variações na composição, adesão, atrito e viscoelasticidade, entre outras propriedades. Como a imagem de fase não é afetada por grandes diferenças de altura, ela proporciona uma observação clara das características finas da amostra que podem ser ocultadas pela topografia rugosa da superfície [17][18][19] .…”
Section: Resultsunclassified
“…Por meio do monitoramento da diferença de fase entre a oscilação da haste e o sinal padrão, que movimenta a cerâmica piezoelétrica durante a varredura, é possível detectar variações na composição, adesão, atrito e viscoelasticidade, entre outras propriedades. Como a imagem de fase não é afetada por grandes diferenças de altura, ela proporciona uma observação clara das características finas da amostra que podem ser ocultadas pela topografia rugosa da superfície [17][18][19] .…”
Section: Resultsunclassified
“…Generally, regions of increased hardness or modulus appear as bright spots in the phase image. However, it has been shown that phase images can be sensitive to the operating parameters including r sp and the free amplitude of oscillation, particularly in a heterogeneous system having different compliances (Bar, et al, 1997). Phase images can even undergo contrast reversals as imaging parameters are changed, making it difficult to assign features in height and phase images to different components based on the direction of phase shift alone (Pickering and Vancso, 1998).…”
Section: Nanogold Labeling Of Fibrinogenmentioning
confidence: 99%
“…Atomic force microscopy (AFM) is a scanning probe technique capable of very high spatial resolution and, when operated in tapping mode, can provide additional information such as differences in local material properties that can then be used to assess phase separation (4). The technique has been used widely in the polymer field (5) over the past two decades for evaluating systems such as polymer blends (6,7), block copolymers (8,9), and nanocomposites (10,11). Beyond the polymer and plastic industries, the technique has been gaining popularity within the pharmaceutical field for the characterization of amorphous solid dispersions (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%